A web based fuzzy expert system preeclampsia pre-diagnosis / Hafizzah Hamizan - Hamizan, Hafizzah (2006)
A preeclampsia caused many cases of hypertension in pregnancy and it's typically develops after the 20th week of gestation and involves a wide spectrum of clinical signs and symptoms. 20* weeks after gestation is quite a heavy months for the pregnant lady. They are difficuh to move easily and most of them face many problems in order to go for gestation check up or go for preeclampsia diagnose. Besides that, most of the pregnant lady has less information about hypertension during pregnancy or specifically preeclampsia. Therefore, this web based fiizzy expert system is developed to overcome this problem. In order to develop this prototype system, fuzzy set theory has been applied in the process of developing. Moreover, the Mamdani fuzzy inference also has been used as the fuzzy inference method. Besides that, the knowledge analysis that has been gathered is also being the important component of this system. All data that gathered from interviews, surveys, observations and printed material are combined to produce a strong knowledge base. Testing are done at the end the coding phase to ensure the end prototype fulfill the objectives of the project and to sort out any errors in the system.